Proposing a Strategic Talent Retention Program to Strengthen the Talent Management System: A Case Study of PT XYZ (Pusat Riset dan Inovasi Nasional, 2024)
PT XYZ is currently undergoing a major digital and operational transformation, necessitating a robust Talent Management System (TMS) capable of retaining its critical managerial talent. The company has successfully met its workforce fulfillment targets , but the sustainability of its talent pipeline remains fragile due to a significant shortfall in filling critical positions and the risk of losing high-potential talent. The fundamental problem is that PT XYZ’s TMS design lacks an integrated, formalized Strategic Talent Retention Program, creating a profound design failure where the focus is reactive (filling vacancies) rather than strategic (securing existing key talent). If this strategic design gap is not addressed promptly, it could compromise PT XYZ's ability to maintain innovation, safety, reliability, and public trust amidst its operational transformation. Therefore, this thesis aims to propose a strategic talent retention program to strengthen PT XYZ’s talent management system, ensuring continuity in critical positions and aligning human capital with long-term digital and operational transformation goals. The research employed a Sequential Exploratory Mixed-Methods Design, combining an initial quantitative analysis of the Annual Employee Survey from 234 talents with subsequent qualitative insights from in-depth interviews with senior leaders. Main findings revealed that while many practices are perceived as strong, three critical dimensions, Work–Life Balance (Mean = 3.08), Career & Development (Mean = 3.23), and Reward & Recognition (Mean = 3.24) require priority improvement to mitigate retention risks. In conclusion, the study proposes an eight-initiative Strategic Talent Retention Program, including priority programs like the Future-Ready Leadership Mobility Program and the Work–Life Integration & Wellbeing Program, thereby transforming the TMS into a proactive strategic tool for sustainable organizational resilience.